Abdominal pumping involvement in the liquid feeding of honeybee. (January 2019) - Zhao, Jieliang; Meng, Fanyue; Yan, Shaoze; Wu, Jianing; Liang, Youjian; Zhang, Yuling
Graphical abstract: Highlights: Drinking behavior of honeybees has a natural link with their abdominal pumping. The real-time motions of internal organs during abdominal pumping are recorded. Honeybee performs a faster pumping rhythm in feeding than that in resting. Abdominal pumping can help honeybees improve their feeding efficiency. Abstract: Honeybee drinking is facilitated by a "mop-like" tongue, which helps honeybees suck in the sucrose solution from the environment. However, the liquid-transport mechanism from the pharynx to the crop, especially the natural link between abdominal pumping and dipping behavior on the sucrose solution intake, remains obscure. A significant increase in abdominal pumping frequency is observed when honeybees drink the sucrose solution. Abdominal pumping exhibits a function other than respiration. This second function assists in driving the sucrose solution from the pharynx to the crop. We combine the experimental measurements using high-speed video and X-ray phase contrast imaging with theoretical modeling to investigate the effect of abdominal pumping in liquid feeding of honeybee. Experimental results show that a honeybee performs abdominal pumping in the abdomen at a faster rhythm during sucrose solution feeding than during other physiological activities. In addition, the period of abdominal pumping is in concordance with that of dipping cycles. Theoretical analysis demonstrates that the abdomen, which is comparable with a micro pump, changes its volume rhythmically. Such expansion reduces pressure in the abdomen, which also reduces pressure in the crop and helps propel the sucrose solution from the pharynx to the crop. Abdominal pumping can help honeybees improve their feeding efficiency and save foraging time. This research work reveals a specific feeding mechanism of insects fed on sucrose solution and opens a new way for the design of microfluidic pump.